Hannibal’s elephants and the Liburnians - Bulić, Nada (Array, 2020)
The second Punic war is a relatively well-known episode from Roman history. Reliable, detailed ancient sources such as Livy and Polybius, however, don’t say much on the topic of Hannibal’s provisions from his native Carthage. One of the questions related to the provisions is where Hannibal’s elephants came from after the battle of Cannae, as after traversing the Etrurian swamp Hannibal only had one elephant left (Livy XXII 2). Immediately after the victory at Cannae Hannibal sends a delegation requesting logistics and the Carthaginian senate decides to send him military aid, among which were 4000 Numidians and 40 elephants (Livy XXIII 11-13). In the meantime, Hannibal penetrates Campania already accompanied by elephants at the Siege of Casilinum (Livy XXIII 18). The authors of this paper believe that Hannibal’s path to Cannae was part of a premeditated military plan, according to which the Carthaginian army needed to pick up supplies near Cannae, with the Liburnians playing an important role in opening channels of communication and supplies. Several facts support this theory, most importantly the following: – one of the few suitable ports that Hannibal could count upon to be less guarded by the Romans than more northern ports, such as Ariminum, is found near Cannae; – an enormous amount of money from Africa is in circulation in Liburnia right at the time of the war with Hannibal; It is known that political entities on the eastern coast of the Adriatic had an anti-Roman political agenda during the time of the second Punic war, coordinating themselves with Macedonia among others, which became an ally of Hannibal and with which Rome went to war in 214 B.C, with which the two Illyrian wars right before and right after the war with Hannibal are related.